2020
DOI: 10.31234/osf.io/p4gm8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-linear age effects in tactile perception from early childhood to adulthood

Abstract: Tactile perception plays a pivotal role in the early stages of human development; however, little is known about tactile function in young children. A better understanding of how tactile function improves with age from early childhood to adulthood is fundamental in understanding atypical tactile experiences in childhood-onset neurodevelopmental disorders, including autism spectrum disorder. In this study, one hundred and forty-two children and adults aged 3–23 years completed a vibrotactile testing battery con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, we did not observe a significant worsening of the amplitude discrimination ability in the simultaneous condition for either cohorts and the difference between sequential and simultaneous amplitude discrimination did not reveal an effect of diagnosis. While it appears that autistic children have inhibitory levels that are categorically different from neurotypical children, as discussed, it could be speculated that, irrespective of diagnosis, an immature inhibitory system in early childhood (Gaetz W. et al, 2014;Port et al, 2017;Saleh et al, 2020) results in worse discrimination ability, as shown in previous behavioural findings (Kaur et al, 2021), and that modulation of the relative timing of stimuli does not further change the threshold. Alternatively, this young age group is expected to show greater perceptual-motor processes.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, we did not observe a significant worsening of the amplitude discrimination ability in the simultaneous condition for either cohorts and the difference between sequential and simultaneous amplitude discrimination did not reveal an effect of diagnosis. While it appears that autistic children have inhibitory levels that are categorically different from neurotypical children, as discussed, it could be speculated that, irrespective of diagnosis, an immature inhibitory system in early childhood (Gaetz W. et al, 2014;Port et al, 2017;Saleh et al, 2020) results in worse discrimination ability, as shown in previous behavioural findings (Kaur et al, 2021), and that modulation of the relative timing of stimuli does not further change the threshold. Alternatively, this young age group is expected to show greater perceptual-motor processes.…”
Section: Discussionmentioning
confidence: 74%
“…TOJ: Temporal Order Judgement. DD: Duration Discrimination Using a customized testing battery that has previously been shown to be appropriate for use in young children (Kaur et al, 2021), our findings show altered tactile perception in early childhood autism on a number of vibrotactile tasks, which suggests reduced cortical inhibition in autism. Specifically, young children with autism showed poorer amplitude discrimination as well as poorer temporal order judgment (e.g., higher thresholds), but not duration discrimination, compared to neurotypical children.…”
Section: Temporal Discriminationmentioning
confidence: 69%
See 3 more Smart Citations